Using data and research to address student misconceptions. (May 2019) - Hoffer, Adam J.
Abstract: This study presents the results of two pedagogical interventions – an assignment using economic data and an assignment requiring a research project – that attempt to dispel economic misconceptions students carry through a typical principles of economics course. Participants completed a wide-ranging questionnaire at the beginning of an academic semester and again at the conclusion of an academic semester. Control and treatment groups were randomly spread across four academic semesters. The results suggest that students who completed the Research project more accurately estimated the percentage of the labor force who earned the minimum wage. While student responses were more accurate, they were, still far from the correct response, on average. The Research project also encouraged students to respond by saying, "I don't know" to the surveyed questions. The data assignment did little to improve student responses.